PROFILE OF ETHNOMATEMATICS IMPLEMENTATION IN MATHEMATICS LEARNING TO STIMULATE STUDENTS' COGNITIVE DEVELOPMENT - Prasetiyo, M. Mahmudi; Sunismi, Sunismi; Walida, Sikky El (Universitas Sembilanbelas November Kolaka, 2025)
The negative perception that mathematics is abstract and rote-oriented leads to low student engagement and cognitive development. This study examines ethnomathematics as a contextual approach that connects formal mathematics with student culture. This study aims to describe the implementation of ethnomathematics, changes in student perceptions, and stimulation of cognitive development. This study uses a descriptive qualitative approach with the study location in the seventh grade of Khairunnas Junior High School. Data were collected through in-depth participatory observation, field notes, interviews, and analysis of learning artifacts. Data analysis was conducted using Spradley's qualitative analysis model. The findings show that the success of implementation is influenced by the teacher's readiness to adapt a contextual approach. Through mentoring, teachers successfully deconstructed the perception that mathematics and culture cannot dialogue, shifting from simply matching formulas to contextual learning adjustments relevant to students' experiences. Students showed more positive changes in their perceptions of mathematics. Students saw mathematics as a skill relevant to their daily experiences. Empirically, ethnomathematics has been proven to improve students' cognitive levels. Cognitive abilities increased from C2 to C3–C4, as observed and confirmed by final assessment results. Ethnomathematics not only increased interest and motivation to learn but also fundamentally stimulated students' cognitive development toward higher-level thinking skills. The results of the study indicate that the integration of local culture has the potential to improve the quality of mathematics learning.